2022
DOI: 10.1029/2022ea002323
|View full text |Cite
|
Sign up to set email alerts
|

Location of Uranium‐Rich Brines Determines the Distribution and Grade of Unconformity‐Related Uranium Deposits

Abstract: Recent fluid inclusion analysis indicates that uranium‐bearing brines were present in both the sandstone and the basement at the time of ore genesis in the Athabasca Basin, Canada. However, the question of how the location of uranium‐rich brines controls the formation of unconformity‐related uranium deposits remains unresolved. In this study, four reactive flow modeling scenarios are designed to address this outstanding issue. Our numerical results confirm that the basement‐hosting uranium‐rich brines are capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For instance, Lin et al [23] examined the effect of fault locations on uranium mineralization. Xu et al [24] confirmed that the location of uranium-bearing brines plays a critical role in ore genesis. However, to the best of our knowledge, no numerical modeling research has been performed to examine the role of paleoregolith in controlling fluid flow and uranium mineralization.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…For instance, Lin et al [23] examined the effect of fault locations on uranium mineralization. Xu et al [24] confirmed that the location of uranium-bearing brines plays a critical role in ore genesis. However, to the best of our knowledge, no numerical modeling research has been performed to examine the role of paleoregolith in controlling fluid flow and uranium mineralization.…”
Section: Introductionmentioning
confidence: 95%
“…The top boundary is 3 km below the surface. Previous numerical studies also employed similar layered models, e.g., [24][25][26][27][28]. A paleoregolith layer occurs below the unconformity, which is intersected and offset by a fault zone.…”
Section: Development Of 2d Reactive Flow Modelsmentioning
confidence: 99%
See 3 more Smart Citations